Paroxysmal hemicrania associated to carotid artery dissection: a case report - Oliveira, Felipe Araújo Andrade (2021)
There are numerous case reports relating trigeminal autonomic cephalalgias to structural injuries. However there is no description of the association between paroxysmal hemicrania and carotid artery dissection.  We describe a previously healthy 63-year-old male presented with the onset of severe, throbbing pain in the right frontal region, lasting between 10 and 30 minutes, with a frequency of approximately two to three attacks per day, which began two days before seeking medical care. Pain was associated with ipsilateral tearing, semiptosis and nasal congestion. A cervical arterial magnetic resonance angiography demonstrated left carotid artery dissection in the C1/C2 segment of the left internal carotid artery. The patient became asymptomatic after indomethacin use. We conclude that the possibility of investigating carotid dissection should be considered in patients with paroxysmal hemicrania.